A new example of circular economy: Waste vegetable oil for cogeneration in wastewater treatment plants. (1st May 2020) - Di Fraia, S.; Massarotti, N.; Prati, M.V.; Vanoli, L.
Graphical abstract: Highlights: The feasibility of using waste vegetable oil for energy production is analyzed. An engine powered by diesel and waste vegetable oil is experimentally investigated. The results are applied to the case study of a real wastewater treatment plant. A feasibility analysis of the proposed system is carried out. The system appears to be economically and environmentally feasible. Abstract: Waste vegetable oil is generated from different sources, such as domestic, commercial and industrial activities, and it requires proper management. Due to the increase in the generation of waste vegetable oil, concern for its management has intensified. The most common management option for waste vegetable oil is the conversion into biodiesel, which improves the chemical-physical characteristics of raw waste vegetable oil for its use but is characterized by significant energy consumption and environmental impact. Therefore, straight waste vegetable oil as fuel, after mechanical pre-treatments and with suitable operational strategy, is suggested in the available literature. In this work, waste vegetable oil from the separate collection is proposed as a source to fuel a combined heat and power unit producing energy for wastewater and sludge treatment plants, which is high energy-demanding. The operation of the combined heat and power unit is analyzed considering data from an experimental campaign carried out to investigate the performance of internal combustion engines powered by waste vegetable oil. Such experimental data are used to carry out the feasibility analysis of a combined heat and power system for an actual wastewater treatment plant located in the Campania region, southern Italy. The system appears to be economically feasible with a simple payback around 3.44 years, a net present value higher than 19.0 M€ and an interest rate of return of 26.7%. Moreover, it produces 70.0% less equivalent carbon dioxide emissions, with respect to a similar system powered by fossil fuels. Therefore, waste vegetable oil as a locally available and renewable energy source may contribute to realize smart and resilient communities, since it improves securing domestic energy supply and waste valorization.